2008
DOI: 10.1055/s-0030-1247822
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Anterior Cruciate Ligament Reconstruction Rehabilitation –Part I: Continuous Passive Motion, Early Weight Bearing, Postoperative Bracing, and Home-Based Rehabilitation

Abstract: Anterior cruciate ligament (ACL) reconstruction is a common surgical knee procedure that requires intensive postoperative rehabilitation by the patient. A variety of randomized controlled trials have investigated aspects of ACL reconstruction rehabilitation. A systematic review of English language level 1 and 2 studies identified 54 appropriate randomized controlled trials of ACL rehabilitation. Topics discussed in this part of the article include continuous passive motion, early weight bearing in motion, post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 27 publications
3
110
0
2
Order By: Relevance
“…20,26 To improve these outcomes, rehabilitation regimens are becoming increasingly evidence-based, and many have incorporated functional testing protocols. 8,14,24,28,35,38 However, the literature has not yet established a relationship between SFT performance and successful return to play or lower reinjury rates. 4 While one previous study found that ACL reconstruction patients with LSI higher than 85% in the single-leg hop and crossover triple hop were more likely to attempt return to play, it did not examine the success of those attempts.…”
Section: Discussionmentioning
confidence: 99%
“…20,26 To improve these outcomes, rehabilitation regimens are becoming increasingly evidence-based, and many have incorporated functional testing protocols. 8,14,24,28,35,38 However, the literature has not yet established a relationship between SFT performance and successful return to play or lower reinjury rates. 4 While one previous study found that ACL reconstruction patients with LSI higher than 85% in the single-leg hop and crossover triple hop were more likely to attempt return to play, it did not examine the success of those attempts.…”
Section: Discussionmentioning
confidence: 99%
“…14 Meanwhile, several studies and reviews conclude that there is no scientific evidence that pain, range of motion, graft stability, or protection from subsequent injury was affected by brace use. [15][16][17][18] A focus of ongoing research in other centers on bracing is aimed at identifying particular groups that may benefit from bracing beyond typical use, for example, skiers. 19 As more well-designed studies are conducted in this area, we may see increased consensus on bracing use.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies included in the previous systematic reviews had evaluated home-based compared with outpatient physical therapy for rehabilitation after ACL reconstruction 1,2 . Despite flaws in reporting and study design that resulted in biases, the studies indicated that a motivated patient could obtain reasonable results with minimally supervised home-based rehabilitation.…”
Section: Home-based Rehabilitationmentioning
confidence: 99%